Randomized trial of ofatumumab and bendamustine versus ofatumumab, bendamustine, and bortezomib in previously untreated patients with high‐risk follicular lymphoma: CALGB 50904 (Alliance). Issue 19 (7th June 2019) - Blum, Kristie A.; Polley, Mei‐Yin; Jung, Sin‐Ho; Dockter, Travis J.; Anderson, Sarah; Hsi, Eric D.; Wagner‐Johnston, Nina; Christian, Beth; Atkins, Jim; Cheson, Bruce D.; Leonard, John P.; Bartlett, Nancy L.
Abstract : Background: This multicenter, randomized phase 2 trial evaluated complete responses (CRs), efficacy, and safety with ofatumumab and bendamustine and with ofatumumab, bendamustine, and bortezomib in patients with untreated, high‐risk follicular lymphoma (FL). Methods: Patients with grade 1 to 3a FL and either a Follicular Lymphoma International Prognostic Index (FLIPI) score of 2 with 1 lymph node >6 cm or an FLIPI score of 3 to 5 were randomized to arm A (ofatumumab, bendamustine, and maintenance ofatumumab) or to arm B (ofatumumab, bendamustine, bortezomib, and maintenance ofatumumab and bortezomib). Results: One hundred twenty‐eight patients (66 in arm A and 62 in arm B) received treatment. The median age was 61 years, and 61% had disease >6 cm; 29% had an FLIPI score of 2, and 71% had an FLIPI score of 3 to 5. In arm A, 86% completed induction, and 64% completed maintenance. In arm B, 66% and 52% completed induction and maintenance, respectively. Dose modifications were required in 65% and 89% in arms A and B, respectively. Clinically significant grade 3 to 4 toxicities included neutropenia (A, 36%; B, 31%), nausea/vomiting (A, 0%; B, 8%), diarrhea (A, 5%; B, 11%), and sensory neuropathy (A, 0%; B, 5%). The estimated CR rates were 62% (95% confidence interval [CI], 50%‐74%) and 60% (95% CI, 47%‐72%) in arms A and B, respectively ( P  = .68). With a median follow‐up of 3.3 years, the estimated 2‐year progression‐free survival (PFS) and overall survival (OS) rates were 80% and 97%, respectively, for arm A and 76% and 91%, respectively, for arm B. Conclusions: The CR rates, PFS, and OS were not improved with the addition of bortezomib to ofatumumab and bendamustine in patients with high‐risk FL. Although grade 3 to 4 toxicities were similar, more patients treated with bortezomib required dose modifications and early discontinuation. Abstract : This randomized, multicenter phase 2 trial demonstrates no benefit with the addition of bortezomib to frontline ofatumumab and bendamustine in patients with high‐risk follicular lymphoma, which is defined as a Follicular Lymphoma International Prognostic Index (FLIPI) score of 3 to 5 or an FLIPI score of 2 with at least 1 lymph node >6 cm. The overall response (OR) rate is 91% with a complete response (CR) rate of 60% and a 2‐year progression‐free survival (PFS) rate of 75.6% for 62 patients treated with ofatumumab, bendamustine, and bortezomib, whereas the OR rate is 95% with a CR of 62% and a 2‐year PFS rate of 80.3% for 66 patients treated with ofatumumab and bendamustine.